los niños trabajadores y sus consecuencias en la mediación pedagógica para el desarrollo de aprendizajes de los estudiantes del octavo al decimo año de educación general básica, de la escuela fiscal mixta Diego de Almagro de la parroquia san Luis de Pambil, cantón Guaranda, provincia Bolívar periodo 2011- 201 - Villafuerte Andrade, Alba Jessenia (2012)
This work we have done prior to obtaining the degree in Science Education, Social, Philosophical and Humanistic. Mention Basic Education. The research is aimed at teachers and especially students of the Eighth to Tenth Year of General Basic Education School Fiscal Mixta "Diego De Almagro. The same consists of the Introduction in which they engage the points of which this research is made, then clearly expose the background, justification, then we specify the sub-problems, we define the problem and describe the sub-problems and objectives to we begin this work, we hypothesized variables and their operationalization. The research includes the following: In Chapter I we find the theoretical framework which is divided into scientific theory, legal framework, contextual and referential theory, giving due weight to clearly understand and can document may be used without any difficulty. Chapter II is composed of the methodological strategies techniques and instruments for data collection, the universe of study and the respective data processing, in the same way we present the different types of methods used in research. Chapter III contains the analysis and interpretation of these results presented in tables and graphs in order to go to prove the hypothesis testing and formulation of conclusions and recommendations. In Chapter IV we present the proposal, which proposes ways to improve the quality of life of children and significantly reduce child labor in this sector.